On-Chip RF Transformer Performance Improvement Technique - Ahmed Saadoon Ezzulddin; Mohammed Hussain Ali; Mutaz Shunasi Abdulwahab (Engineering and Technology Journal, 2010)
In this work, a proposed on-chip radio-frequency (RF) transformer design andlayout technique is presented to achieve high magnetic coupling coefficient andlow insertion loss by segmenting and interleaving wide primary and secondarymetal traces. Additional advantage of such technique is the mitigation of proximityeffect and current crowding. The proposed technique is verified and tested for asquare transformer, with different segmentation structures, using EMSightsimulator of Microwave Office 2007 (version 7.5) RF/Microwave software tools.By using this design and layout technique, the magnetic coupling coefficientimproves from 0.49 to over 0.72 and lowers the minimum insertion loss from1.56 dB to 1.18 dB at 4.5 GHz center frequency.